The leukemic oncogene EVI1 hijacks a MYC super-enhancer by CTCF-facilitated loops - Ottema, Sophie; Mulet-Lazaro, Roger; Erpelinck-Verschueren, Claudia; van Herk, Stanley; Havermans, Marije; Arricibita Varea, Andrea; Vermeulen, Michael; Beverloo, H. Berna; Gröschel, Stefan; Haferlach, Torsten; Haferlach, Claudia; J. Wouters, Bas; et al. (Nature Communications, 2021)
Chromosomal rearrangements are a frequent cause of oncogene deregulation in human malignancies. Overexpression of EVI1 is found in a subgroup of acute myeloid leukemia (AML) with 3q26 chromosomal rearrangements, which is often therapy resistant. In AMLs harboring a t(3;8)(q26;q24), we observed the translocation of a MYC super-enhancer (MYC SE) to the EVI1 locus. We generated an in vitro model mimicking a patient-based t(3;8)(q26;q24) using CRISPR-Cas9 technology and demonstrated hyperactivation of EVI1 by the hijacked MYC SE. This MYC SE contains multiple enhancer modules, of which only one recruits transcription factors active in early hematopoiesis. This enhancer module is critical for EVI1 overexpression as well as enhancer-promoter interaction. Multiple CTCF binding regions in the MYC SE facilitate this enhancer-promoter interaction, which also involves a CTCF binding site upstream of the EVI1 promoter. We hypothesize that this CTCF site acts as an enhancer-docking site in t(3;8) AML. Genomic analyses of other 3q26-rearranged AML patient cells point to a common mechanism by which EVI1 uses this docking site to hijack enhancers active in early hematopoiesis.